Pengharapan Baru: Menginterpretasi Ulangan 1:1-8 dengan Pendekatan Kanonis Brevard S. Childs - Roy Charly HP Sipahutar (Institut Agama Kristen Negeri Toraja, 2020)
This paper is an attempt to find out the canonical meaning of the insertion of the text of Deuteronomy 1: 1-8 in the overall framework of Deuteronomy. The method used in this research is canonical hermeneutics developed by Brevard S. Childs, this approach enables the interpreter to see the intent of the editor of the Scriptures in the preparation of text sequences in such a way as to the perspective of the final canon. The canonical analysis shows that Deuteronomy 1: 1-8 is the initial part of the minor form (chapters 1-4) that is deliberately inserted and placed at the front as a close link to the previous book (even the first four books of the holy book) and is both an introduction and legitimacy of authority Deuteronomy even for the whole Deuteronomic History. This text comes from the editor of the exile and gives a message of new hope for the exiled Israeli community.This paper is an attempt to find out the canonical meaning of the insertion of the text of Deuteronomy 1: 1-8 in the overall framework of Deuteronomy. The method used in this research is canonical hermeneutics developed by Brevard S. Childs, this approach enables the interpreter to see the intent of the editor of the Scriptures in the preparation of text sequences in such a way as to the perspective of the final canon. The canonical analysis shows that Deuteronomy 1: 1-8 is the initial part of the minor form (chapters 1-4) that is deliberately inserted and placed at the front as a close link to the previous book (even the first four books of the holy book) and is both an introduction and legitimacy of authority Deuteronomy even for the whole Deuteronomic History. This text comes from the editor of the exile and gives a message of new hope for the exiled Israeli community.